Przygotowanie dalsze i bliższe do sakramentu pokuty i pojednania - Biela, Bogdan (Studia Pastoralne, 2007)
In the awareness of many faithful the sacrament of penance is but a sheer formality, if not a magical way of getting rid of sin. This attitude manifests itself in the way preparation is made for this sacrament. Quite often the major focus is on reading an examination of conscience from a book of prayers and confessing one’s sins, whereas the other conditions of adequate and fruitful participation in the sacrament: penitence, contrition, resolution to amend one’s life and penance are performed only on a formal level. While preparing the faithful for the sacrament of penance and reconciliation one should, therefore, speak of indirect and direct preparation. As far as the ministry of penance, one can clearly see specific conclusions and tasks. The main source of the present crisis of this sacrament may be found in reducing the whole penance practice solely to individual confession at the cost of non-sacramental forms of taking sins away. The major postulate is therefore to celebrate the liturgy of the sacrament of penance in the context of the whole penance practice of the Church. For the preparation for the sacrament of penance and reconciliation cannot be separated from the holistic context of penance as the major life attitude of everyday conversion understood here as the biblical metanoia. Moreover, the common practise of celebrating the sacrament may make one conclude that the character of penance is purely personal and that the purpose is to re-establish a correct relation between an individual and God. The reality is that a man does not live in perfect isolation from one’s brothers and sisters. One’s salvation takes place in a human environment. Therefore one can enumerate these most vital pastoral postulates preparing for the sacrament of penance: shaping the sensibility of the faithful to an individual and social character of sin and conversion, emphasizing the communal element in preparation for the liturgy of the sacrament of penance and understanding a confessor’s involvement in shaping the social and ecclesial attitude of a penitent.